2011
DOI: 10.1080/10874208.2011.570689
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SMR and Theta/Beta Neurofeedback on Reaction Times, Spatial Abilities, and Creativity

Abstract: Neurofeedback training (NFT) has been demonstrated to be a useful, inexpensive, nonpharmacological tool in the treatment of attention deficit hyperactivity disorder and epilepsy in humans. Different neurofeedback training protocols have been associated with positive effects on performance in sports, creativity, memory, and simple reaction time tasks. During NFT, individuals receive visual or acoustic feedback of their brain oscillations, which are recorded by electroencephalogram (EEG). Through operant conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
61
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 47 publications
7
61
0
1
Order By: Relevance
“…For example, Egner and Gruzelier (2001) observed, after SMR NFT, an increased P300b amplitude at frontal, central, and parietal sites in the auditory oddball task, as well as reductions in commission errors and reaction time variability on the Test of Variables of Attention. Similarly, Doppelmayr and Weber (2011) demonstrated that participants exhibited improved performance on spatial rotation, simple, and choice reaction time tasks, suggesting advanced visuospatial ability after augmented SMR NFT. Augmented SMR NFT also improved the memory and attentional performance, accompanied by increased N1 and P3 event-related potential amplitudes (Kober et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Egner and Gruzelier (2001) observed, after SMR NFT, an increased P300b amplitude at frontal, central, and parietal sites in the auditory oddball task, as well as reductions in commission errors and reaction time variability on the Test of Variables of Attention. Similarly, Doppelmayr and Weber (2011) demonstrated that participants exhibited improved performance on spatial rotation, simple, and choice reaction time tasks, suggesting advanced visuospatial ability after augmented SMR NFT. Augmented SMR NFT also improved the memory and attentional performance, accompanied by increased N1 and P3 event-related potential amplitudes (Kober et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Arns, Drinkenburg and Kenemans (2012) showed that neurofeedback training significantly improves attention deficit, hyperactivity, impulsivity, and depression complaints. Doppelmayr and Weber (2011) also showed that neurofeedback increases the reaction rate and improving visual-spatial ability. In addition to these studies, the impacts of neurofeedback was shown on changes in the reaction time (Drechsler et al, 2007), hemispherical performance in left partial areas, and increase in attention and response time (Beauregard & Levesque, 2006;Cho et al, 2004), main improvements in sustainable control of the symptoms of ADHD, lack of emotional instability, and amount of homework (Lubar, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies showed that increasing SMR power was associated with reduced somatosensory and motor interference in an attention-demanding task (Egner & Gruzelier, 2001. Furthermore, augmented SMR NFT was beneficial to declarative memory (Hoedlmoser et al, 2008), mental rotation (Doppelmayr & Weber, 2011), novel music performance in children (Gruzelier, Foks, Steffert, Chen, & Ros, 2014), and acting performance with a greater subjective flow state (Gruzelier et al, 2010). In addition, Ros et al (2009) observed a significant reduction of simulated cataract surgical time due to the improvement in visuo-motor skills following augmented SMR training, which was accompanied by a reduction in anxiety.…”
Section: Discussionmentioning
confidence: 99%